Ashes to ashes, time to time: Parental time discounting and its role in the intergenerational transmission of smoking - Philipp Hübler; Andreas Kucher (Universität Augsburg, Institut für Volkswirtschaftslehre, 2016)
Intergenerational correlations of risky health behaviors such as tobacco consumption are well established. However, there is still limited empirical evidence about the underlying process through which the transmission is driven. This paper aims at analyzing parental time discounting and its role in the intergenerational transmission of smoking. The analysis is based on longitudinal data from the German Socio-Economic Panel (SOEP) for the years 2006, 2008 and 2010. We use a linear panel regression model to estimate the child's likelihood of being a current smoker. The SOEP contains a great many of socio-economic characteristics and also meaningful measures of individual discounting behavior, namely, general patience and impulsivity. This enables us to distinguish between time preference and self-control, respectively. We find significant effects of time preference for both, mothers and fathers. That is, an increasing level of patience of parents is associated with a lower smoking probability of the child. Regarding self-control, only father's impulsivity has a similar decreasing impact. Stratifying the sample by gender reveals substantial mother-daughter, mother-son and father-son effects. Additionally, we estimate the influence of health-related mediating factors such as parental smoking and alcohol consumption. It turns out that role modeling as well as time discounting of the parents are highly relevant in this transmission process.
urn:nbn:de:bvb:384-opus4-710902
Keywords: D9; D10; I12; J13; 330; family economics; intergenerational transmission; smoking; time discounting; time preference; patience; self-control; impulsivity